2006
DOI: 10.1128/mcb.00048-06
|View full text |Cite
|
Sign up to set email alerts
|

ATR-Dependent Phosphorylation of DNA-Dependent Protein Kinase Catalytic Subunit in Response to UV-Induced Replication Stress

Abstract: Phosphorylation of the DNA-dependent protein kinase catalytic subunit (DNA-PKcs) upon ionizing radiation (IR) is essential for cellular radioresistance and nonhomologous-end-joining-mediated DNA doublestrand break repair. In addition to IR induction, we have previously shown that DNA-PKcs phosphorylation is increased upon camptothecin treatment, which induces replication stress and replication-associated doublestrand breaks. To clarify the involvement of DNA-PKcs in this process, we analyzed DNA-PKcs phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
119
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 37 publications
13
119
1
Order By: Relevance
“…In addition, Nu7441 but not the ATM kinase inhibitor Ku55933 attenuated mitotic DNA-PKcs phosphorylation at Thr-2609. We have reported previously that DNA-PKcs Thr-2609 phosphorylation is mediated by ATM and ATR kinases in response to IR and UV-induced replication stress, respectively (8,9). The result in Fig.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In addition, Nu7441 but not the ATM kinase inhibitor Ku55933 attenuated mitotic DNA-PKcs phosphorylation at Thr-2609. We have reported previously that DNA-PKcs Thr-2609 phosphorylation is mediated by ATM and ATR kinases in response to IR and UV-induced replication stress, respectively (8,9). The result in Fig.…”
Section: Discussionmentioning
confidence: 59%
“…We have previously reported that DNA-PKcs kinase autophosphorylates itself at Ser-2056 in response to IR (7), whereas ATM and ATR kinases are required for DNA-PKcs phosphorylation at Thr-2609 (8,9). To determine whether ATM is involved in mitotic DNA-PKcs phosphorylation, ATM-proficient 1BR3 and deficient AT5 human fibroblasts were arrested in mitosis and were analyzed for DNA-PKcs phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this, it is likely that DNA-PK, which normally regulates repair of DSBs by NHEJ, also responds to DSBs induced during replication stress. It has been previously reported that DNA-PK undergoes auto-phosphorylation after the treatment of cells with genotoxic agents such as UV, hydroxyurea and the TOP1 inhibitor, camptothecin 15,16 . In addition, DNA-PK becomes rapidly activated following nucleotide depletion when Chk1 activity is compromised 17 .…”
Section: Alchemix Induces a Marked Atr-dependent Dna Damage Response mentioning
confidence: 99%